An etiological dilemma in osteomyelitis: A case report - Aparna Muraleedharan (Wolters Kluwer Medknow Publications, 2015)
Osteomyelitis is an acute or chronic inflammatory process that can involve cortical and trabecular aspects of bone or bone marrow. This case report describes an interesting presentation of chronic suppurative osteomyelitis in a 22-year-old male patient who visited the dental clinic with a chief complaint of facial asymmetry and esthetic concern only. The history, examination, radiographic and histopathological investigations contributed to the diagnosis of chronic suppurative osteomyelitis; however, the etiology remained a dilemma. Treatment included surgical debridement and curettage followed by antibiotics.